Health effects associated with waterpipe smoking. (6th February 2015) - El-Zaatari, Ziad M; Chami, Hassan A; Zaatari, Ghazi S
Abstract : Objective: It is widely held that waterpipe smoking (WPS) is not associated with health hazards. However, several studies have documented the uptake of several toxicants and carcinogens during WPS that is strongly associated with harmful health effects. This paper reviews the literature on the health effects of WPS. Data sources: Three databases-PubMed, MEDLINE and EMBASE-were searched until August 2014 for the acute and long-term health effects of WPS using the terms 'waterpipe' and its synonyms (hookah, shisha, goza, narghileh, arghileh and hubble-bubble) in various spellings. Study selection: We included original clinical studies, case reports and systematic reviews and focused on clinical human studies. ∼10% of the identified studies met the selection criteria. Data extraction: Data were abstracted by all three authors and summarised into tables. Abstracted data included study type, results and methodological limitations and were analysed jointly by all three authors. Data synthesis: WPS acutely leads to increased heart rate, blood pressure, impaired pulmonary function and carbon monoxide intoxication. Chronic bronchitis, emphysema and coronary artery disease are serious complications of long-term use. Lung, gastric and oesophageal cancer are associated with WPS as well as periodontal disease, obstetrical complications, osteoporosis and mental health problems. Conclusions: Contrary to the widely held misconception, WPS is associated with a variety of adverse short-term and long-term health effects that should reinforce the need for stronger regulation. In addition, this review highlights the limitations of the published work, which is mostly cross-sectional or retrospective. Prospective studies should be undertaken to assess the full spectrum of health effects of WPS, particularly in view of its growing popularity and attractiveness to youth.